2013
DOI: 10.1002/ggge.20150
|View full text |Cite
|
Sign up to set email alerts
|

The P and S wave velocity structure of the mantle beneath eastern Africa and the African superplume anomaly

Abstract: P and S relative arrival time residuals from teleseismic earthquakes recorded on over 60 temporary AfricaArray broadband seismic stations deployed in Uganda, Tanzania, and Zambia between 2007 and 2011 have been inverted, together with relative arrival time residuals from earthquakes recorded by previous deployments, for a tomographic image of mantle wave speed variations extending to a depth of 1200 km beneath eastern Africa. The image shows a low‐wave speed anomaly (LWA) well developed at shallow depths (100–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
83
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 81 publications
17
83
1
Order By: Relevance
“…The MTZ exhibits a normal thickness beneath Cameroon (Reusch et al 2011). Mulibo and Nyblade (2013) determined P and S wave tomography under East Africa down to 1200 km depth (Fig. Mulibo and Nyblade (2013) determined P and S wave tomography under East Africa down to 1200 km depth (Fig.…”
Section: African Hotspotsmentioning
confidence: 95%
See 2 more Smart Citations
“…The MTZ exhibits a normal thickness beneath Cameroon (Reusch et al 2011). Mulibo and Nyblade (2013) determined P and S wave tomography under East Africa down to 1200 km depth (Fig. Mulibo and Nyblade (2013) determined P and S wave tomography under East Africa down to 1200 km depth (Fig.…”
Section: African Hotspotsmentioning
confidence: 95%
“…5.7), which are associated with the African superplume (Maruyama 1994;Montelli et al 2006;Chang and Van der Lee 2011;Davies et al 2012;Hansen et al 2012;Brandt 2013;Mulibo and Nyblade 2013;. 5.7), which are associated with the African superplume (Maruyama 1994;Montelli et al 2006;Chang and Van der Lee 2011;Davies et al 2012;Hansen et al 2012;Brandt 2013;Mulibo and Nyblade 2013;.…”
Section: African Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…5.7), which are associated with the African superplume (Maruyama 1994;Ritsema et al 1999;Zhao 2001bZhao , 2004Montelli et al 2006;Chang and Van der Lee 2011;Davies et al 2012;Hansen et al 2012;Brandt 2013;Mulibo and Nyblade 2013;. Large low-V zones are visible from the surface down to about 1000 km under the Afar, Lake Victoria, and East Africa hotspots, which seem to connect with the low-V zones in the lower mantle (Fig.…”
Section: African Hotspotsmentioning
confidence: 90%
“…The excess temperature in the low-V zone is ~ 150-300 K. The depth extent of the low-V anomaly indicates that the African superplume is likely a whole mantle structure. A superplume extending from the CMB to the surface implies an origin for the Cenozoic extension, volcanism and plateau uplift in eastern Africa rooted in the dynamics of the lower mantle (Mulibo and Nyblade 2013). Hilton et al (2011) reported helium isotope ratios of lavas and tephra of the Rungwe Volcanic Province in southern Tanzania.…”
Section: African Hotspotsmentioning
confidence: 99%